Prototyping a Hurricane-Flood-Landslide-Continuum Prediction System: A CI-FLOW Contribution to North Carolina and Broader Coastal Regions - Hong, Yang; Gourley, J.J.; VergaraArrieta, Humberto J.; Liao, Zonghu; Van Cooten, Suzanne; Kelleher, Kevin (My University, 2009)
A partnership between NASA and the US Agency for International Development (USAID) is examining prototyping a hurricane-flood-landslide continuum as part of CI-FLOW (Coastal and Inland Flooding Observation and Warning project). Using high resolution satellites, hydrological data can be used to monitor global flooding. The Terra and Aqua satellites use a key instrument called MODIS (Moderate Resolution Imaging Spectroradiometer) to map flood inundation. Aster flood maps are used to calibrate hydrologic modeling. Additionally, inland river flow and storm surge modeling is being done as a part of CI-FLOW. Part of the problem with the models is determining how to calibrate them effectively. Researchers examined a full spectrum of data calibration techniques. The guided DREAM technique performed the best in terms of minimizing bias. They also examined Hurricane Floyd, and, using a discharge simulation, the guided DREAM preformed well. Landslides can accompany floods, and LIDAR (Light Detection and Ranging) data can be useful in examining slope stability and rainfall. In order to effectively manage hazards, an integrated approach is necessary, using hydrological data and flood prediction systems. Recently, the prediction system has been implemented successfully.
Keywords: Hurricanes; Emergency management; NCEM; Emergency disaster